Silicon-containing negative electrode material, preparation method and application thereof
Patent Information
- Application Number
- CN202510562495.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-30
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]目前对于硅基材料的研究大多集中在提升循环性能、减少材料体积膨胀方面,在改善动力学方面的研究较少,而且工艺路线复杂,对于动力学的改善效果也存在明显的不足之处
[0097](1)本发明提供的含硅负极材料中,通过硅基内核及其上包覆的碳层、离子传输型人造SEI膜的设计和相互复配,减少了电解液在硅负极表面的去溶剂化作用,锂离子在界面传输的势垒得到了显著降低,使所述含硅负极材料具有优异的动力学性能,有效提升了包含其的锂离子电池的首周脱锂容量和不同倍率下的循环性能,使电池具有更低的阻抗、更高的首效和更快的充电速率,尤其在快充性能方面得到明显改善。
Smart Images

Figure BDA0005384998480000261 
Figure BDA0005384998480000271
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery materials technology, specifically relating to a silicon-containing anode material, its preparation method, and its application. Background Technology
[0002] Lithium-ion batteries possess advantages such as long cycle life, high energy density, and low self-discharge rate, and are widely used in electric vehicles, mobile electronic products, artificial intelligence, energy storage systems, aerospace, and many other fields. Lithium-ion batteries are mainly assembled from a positive electrode, a negative electrode, a separator, and an electrolyte. The negative electrode material has a significant impact on the energy density and rate performance of lithium-ion batteries. Currently, commercially available battery negative electrode materials are mainly graphite; however, graphite's theoretical specific capacity is approximately 372 mAh / g, which is relatively low, limiting the development of lithium-ion batteries towards higher energy density.
[0003] Compared to graphite, silicon-based materials offer several advantages, including higher theoretical lithium intercalation capacity, suitable operating voltage, and abundant silicon reserves in the Earth's crust. However, current silicon-based materials cannot yet meet the requirements for high energy density and high kinetics. Because the lithium intercalation potential of silicon-based anode materials is higher than that of graphite anode materials, during battery charging, lithium ions preferentially intercalate into the silicon anode before the graphite anode. This means that the lithium intercalation rate of silicon-based materials is crucial to the battery's kinetic performance.
[0004] Improving the performance of silicon-based materials has been a research hotspot in the industry in recent years. For example, CN118380575A discloses a silicon-based anode material with a composite artificial SEI film. The preparation method is as follows: S1, preparing a reactive copolymer, wherein the reactive copolymer is obtained by copolymerization of a bromochlorine organic compound and an acrylonitrile compound containing methylamino group; S2, dissolving the reactive copolymer in an organic solvent to obtain a copolymer solution, then mixing the copolymer solution with a metal hydroxide and dispersing it to obtain a dispersion solution; S3, applying the dispersion solution to the surface of the silicon anode material, and drying the dispersion solution on the surface of the silicon anode material to obtain the silicon-based anode material with the composite artificial SEI film; by using a mixture of a bromochlorine organic compound and a reactive copolymer containing methylamino acrylonitrile compound with a metal hydroxide as the composite artificial SEI film on the surface of the silicon anode material, the adhesion between the SEI film and the silicon anode material is improved, which can improve the dynamic performance, rate performance, cycle performance and safety performance of lithium batteries. CN117976878A discloses a silicon anode material, comprising a silicon-based material and a polymer coated thereon. The polymer is polymerized from monomers and contains amino, thiol, carboxyl, and carbonyl functional groups. This polymer coating can alleviate the volume expansion of the silicon anode. The introduction of organic functional groups can improve the stability of the polymer coating and improve the wetting ability of the anode sheet, thereby improving the kinetic performance of the silicon anode, reducing side reactions at the electrolyte-anode interface, and improving the cycle performance of the battery. CN118472205A discloses a silicon anode active material, comprising a silicon-based material and an artificial SEI film coated on its surface. The artificial SEI film comprises a copolymer containing 1,3-dioxolane groups and sulfonyl fluoride groups in its molecular structure, giving the copolymer good flexibility and effectively alleviating the volume expansion of the silicon-based material, avoiding problems such as SEI film rupture caused by the volume expansion of the silicon-based material, which leads to the degradation of battery cycle performance.
[0005] Current research on silicon-based materials largely focuses on improving cycling performance and reducing volume expansion, with limited research on improving kinetics. Furthermore, the complex manufacturing processes used in these studies also have significant limitations in improving kinetics. Therefore, developing silicon-based materials with superior kinetic properties is a key research focus in this field. Summary of the Invention
[0006] To address the shortcomings of existing technologies, the present invention aims to provide a silicon-containing anode material, its preparation method, and its application. By designing and combining a silicon-based core, a carbon layer coated on it, and an ion-transporting artificial SEI film, the barrier for lithium-ion transport at the interface is significantly reduced, giving the silicon-containing anode material significantly improved kinetic performance. This effectively improves the cycle performance of lithium-ion batteries at different rates and significantly enhances fast-charging performance.
[0007] To achieve this objective, the present invention adopts the following technical solution:
[0008] In a first aspect, the present invention provides a silicon-containing anode material, the silicon-containing anode material comprising a silicon-based core and a carbon layer disposed on the silicon-based core and an ion-transporting artificial SEI film, wherein the carbon layer is located between the silicon-based core and the ion-transporting artificial SEI film.
[0009] The silicon-containing anode material provided by this invention has a three-layer structure. The inner layer is a silicon-based core, which can act as a lithium storage layer and has a significant high capacity advantage. The middle layer is a carbon layer, which can enhance the overall conductivity of the silicon-containing anode material, suppress the volume expansion of the silicon-based core, and reduce the reaction between the electrolyte and the silicon-based core. The outer layer is an ion-transporting artificial SEI film, which has excellent electrolyte affinity, can increase the lithium-ion desolvation process, increase the lithium-ion interfacial transport rate at the anode, and reduce the interfacial transport barrier of lithium-ion on the surface of the silicon-containing anode material, thus significantly improving the kinetic performance of the silicon-containing anode material. Through the specific three-layer structure design and the compounding effect between the layers, this invention reduces the desolvation effect of the electrolyte on the silicon anode surface, significantly lowers the lithium-ion transport barrier at the interface, and gives the silicon-containing anode material excellent kinetic performance. This effectively improves the initial efficiency, first-cycle delithiation capacity, and cycle performance at different rates of the lithium-ion battery containing it, resulting in lower impedance, higher initial efficiency, and faster charging rate, and significantly improved fast-charging performance.
[0010] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. The purpose and beneficial effects of the present invention can be better achieved and realized through the following preferred technical solutions.
[0011] Preferably, the ion-transporting artificial SEI membrane comprises ion-transporting materials and / or conductive materials.
[0012] In this invention, the components of the ion-transporting artificial SEI membrane include three parallel technical solutions: pure ion-transporting material, pure conductive material, and a combination of ion-transporting material and conductive material. For the parallel technical solution of "combination of ion-transporting material and conductive material", the ion-transporting material and conductive material can be combined in any proportion. That is, the mass percentage of ion-transporting material in the ion-transporting artificial SEI membrane is 0-100%, for example, it can be 0, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, or 100%, as well as specific values between the above values. Due to space limitations and for the sake of brevity, this invention will not exhaustively list the specific values included in the range. And / or, the mass percentage of conductive material in the ion-transporting artificial SEI film is 0-100%, for example, it can be 0, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or 100%, and specific values between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values included in the range.
[0013] The ion transport material comprises an inorganic substance with excellent ion-conducting ability. Preferably, the ion transport material comprises any one or a combination of at least two of the following: lithium salt, lithium oxide, transition metal oxide, transition metal phosphide, transition metal sulfide, half-metal oxide, elemental phosphorus, elemental sulfur, and other solid electrolytes.
[0014] More preferably, the ion transport material comprises any one or a combination of at least two of the following: lithium carbonate, lithium silicate, lithium metasilicate, lithium phosphate, lithium metaphosphate, lithium hypophosphite, lithium borate, lithium titanate, lithium oxide, lithium fluoride, lithium aluminate, lithium phosphide, lithium sulfide, lithium nickelate, calcium oxide, zinc oxide, aluminum oxide (aluminum oxide), zirconium oxide, zirconium nitride, zirconium phosphide, molybdenum oxide, molybdenum nitride, molybdenum phosphide, molybdenum sulfide, molybdenum borate, silicon suboxide, silicon dioxide, titanium dioxide, elemental phosphorus, elemental sulfur, other oxide solid electrolytes, and other sulfide solid electrolytes.
[0015] Preferably, the average particle size of the ion transport material is 1-1000 nm, for example, it can be 2 nm, 5 nm, 8 nm, 10 nm, 20 nm, 50 nm, 80 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm or 900 nm, as well as specific values between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values included in the range.
[0016] Preferably, the conductive material includes any one or a combination of at least two of graphene, carbon nanotubes, conductive carbon black, amorphous carbon, soft carbon, and hard carbon.
[0017] Preferably, the ion-transporting artificial SEI membrane comprises an ion-transporting material and / or a conductive material, and the ion-transporting artificial SEI membrane has at least one of the following structures: A-D.
[0018] Structure A: Composed of ion transport materials;
[0019] Structure B: Composed of conductive materials;
[0020] Structure C: The conductive material is distributed within the ion transport material;
[0021] Structure D: The ion transport material is distributed within the conductive material.
[0022] Preferably, based on the total mass of the silicon-based core and carbon layer as 100%, the mass of the ion-transporting artificial SEI film is 0.01%-15%, for example, it can be 0.02%, 0.05%, 0.08%, 0.1%, 0.2%, 0.4%, 0.5%, 0.6%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, or 14%, as well as specific values between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values included in the range.
[0023] Preferably, the thickness of the carbon layer is 1-30nm, for example, it can be 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 10nm, 12nm, 15nm, 18nm, 20nm, 22nm, 25nm or 28nm, as well as specific values between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values included in the range.
[0024] In this invention, the carbon layer is located between the silicon-based core and the ion-transporting artificial SEI film. It enhances conductivity and works synergistically with the ion-transporting artificial SEI film to suppress the volume expansion of the silicon-based core, thereby improving kinetic and cycling performance. If the carbon layer is too thin, it hinders the improvement of conductivity; if the carbon layer is too thick, the proportion of carbon in the silicon-containing anode material increases, resulting in a loss of the high-capacity advantage of the silicon-containing anode material.
[0025] Preferably, with the mass of the silicon-based core being 100%, the mass of the carbon layer is 0.01%-10%, for example, it can be 0.02%, 0.05%, 0.08%, 0.1%, 0.2%, 0.4%, 0.5%, 0.6%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 5%, 6%, 7%, 8%, or 9%, as well as specific values between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values included in the range.
[0026] Preferably, the silicon-based core comprises any one or a combination of at least two of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite, and silicon alloy.
[0027] Preferably, the median particle size of the silicon-containing anode material is 1-30 μm, for example, it can be 1.5 μm, 2 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 22 μm, 25 μm or 28 μm, as well as specific particle sizes between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific particle sizes included in the range, and 2-20 μm is further preferred.
[0028] Preferably, the specific surface area of the silicon-containing anode material is 0.1-20 m². 2 / g, for example, can be 0.2m 2 / g, 0.5m 2 / g, 0.8m 2 / g、1m 2 / g、2m 2 / g、4m 2 / g、5m 2 / g、6m 2 / g、8m 2 / g, 10m 2 / g、12m 2 / g、14m 2 / g, 15m 2 / g, 16m 2 / g or 18m 2 / g, and specific point values between the above point values. Due to space limitations and for the sake of brevity, this invention will not exhaustively list the specific point values included in the range, but further preferably 1-10m. 2 / g.
[0029] Secondly, the present invention provides a method for preparing a silicon-containing anode material as described in the first aspect, wherein the preparation method employs an atomic layer deposition-like method and includes the following steps:
[0030] (1) A carbon layer is set on a silicon-based core to obtain a carbon-coated silicon-based material;
[0031] (2) The carbon-coated silicon-based material, ion transport medium precursor, dispersant and solvent are mixed and dispersed in a first shear dispersion device to obtain a dispersion.
[0032] (3) The dispersion is dried in a second shear dispersion drying device under heat flow conditions to form microdroplets and obtain powder;
[0033] (4) The powder is subjected to dynamic heat treatment in a dynamic heat treatment device to obtain the silicon-containing anode material.
[0034] In this invention, the preparation method of the silicon-containing anode material involves obtaining an ion-transporting artificial SEI film through steps (2)-(4). This film utilizes atomic layer deposition (ALD) surface modification technology, where high shear force is used to uniformly disperse the ion-transporting medium precursor and the carbon-coated silicon-based material. Subsequently, the ion-transporting medium precursor is uniformly coated onto the surface of the carbon-coated silicon-based material through instantaneous drying. After dynamic heat treatment, a dense, complete, and uniformly coated ion-transporting artificial SEI film is formed. This preparation method is simple to operate, low in cost, and easy to scale up, significantly improving the performance of the silicon-containing anode material and possessing broad application prospects.
[0035] Preferably, the method for setting the carbon layer includes physical vapor deposition and / or chemical vapor deposition, more preferably chemical vapor deposition (CVD).
[0036] Preferably, the carbon source used in the chemical vapor deposition includes any one or a combination of at least two of acetylene, ethylene, methane, and ethane.
[0037] Preferably, the temperature of the chemical vapor deposition is 400-1000℃, for example, it can be 450℃, 480℃, 500℃, 520℃, 550℃, 580℃, 600℃, 650℃, 700℃, 750℃, 800℃, 850℃, 900℃, 950℃ or 980℃, as well as specific values between the above points. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values included in the range.
[0038] Preferably, the pressure of the chemical vapor deposition is 1-10 MPa, for example, it can be 1.5 MPa, 2 MPa, 2.5 MPa, 3 MPa, 3.5 MPa, 4 MPa, 4.5 MPa, 5 MPa, 5.5 MPa, 6 MPa, 6.5 MPa, 7 MPa, 7.5 MPa, 8 MPa, 8.5 MPa, 9 MPa or 9.5 MPa, as well as specific values between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values included in the range.
[0039] Preferably, the chemical vapor deposition time is 0.5-8h, for example, it can be 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h or 7.5h, as well as specific point values between the above points. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific point values included in the range.
[0040] Preferably, the ion transport medium precursor comprises an ion transport material and / or a conductive material.
[0041] The types and parameters of the ion transport materials and conductive materials are as described in the first aspect, and for the sake of brevity, they will not be repeated here.
[0042] Preferably, the ion transport medium precursor can be any one of ion transport materials or conductive materials, or a combination of ion transport materials and conductive materials. For the parallel technical solution of "combination of ion transport materials and conductive materials", the ion transport materials and conductive materials can be combined in any proportion. More preferably, the mass ratio of the ion transport material to the conductive material is 1:(0.01-20), for example, it can be 1:0.05, 1:0.1, 1:0.2, 1:0.4, 1:0.5, 1:0.6, 1:0.8, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18 or 1:19, etc., and more preferably 1:(0.05-10).
[0043] Preferably, based on the mass of the carbon-coated silicon-based material as 100%, the mass of the ion transport medium precursor is 0.01%-15%, for example, it can be 0.02%, 0.05%, 0.08%, 0.1%, 0.2%, 0.4%, 0.5%, 0.6%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, or 14%, as well as specific values between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values included in the range.
[0044] Preferably, the dispersant comprises any one or a combination of at least two of carboxymethyl cellulose salt, alginate, (meth)acrylic acid homopolymer salt, and (meth)acrylic acid copolymer salt.
[0045] In this invention, the term (meth)acrylic acid means acrylic acid and / or methacrylic acid.
[0046] Preferably, the cations in the carboxymethyl cellulose salt, alginate, (meth)acrylic acid homopolymer salt, and (meth)acrylic acid copolymer salt each independently include any one or a combination of at least two of lithium ions, sodium ions, potassium ions, calcium ions, and zinc ions.
[0047] Preferably, based on the mass of the carbon-coated silicon-based material as 100%, the mass of the dispersant is 0.01%-5%, for example, it can be 0.02%, 0.05%, 0.08%, 0.1%, 0.2%, 0.4%, 0.5%, 0.6%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, or 4.5%, as well as specific values between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values included in the range.
[0048] Preferably, the solvent is water.
[0049] Preferably, with the mass of the carbon-coated silicon-based material as 100%, the mass of the solvent is 50%-500%, for example, it can be 80%, 100%, 150%, 200%, 250%, 300%, 350%, 400% or 450%, and specific values between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values included in the range.
[0050] Preferably, the first shearing and dispersing device includes any one or a combination of at least two of a disperser, a mixer, a homogenizer, and a rotor homogenizing circulation pump, and more preferably a combination of a disperser (high-speed disperser) and a rotor homogenizing circulation pump.
[0051] Unlike traditional ball milling / sand milling processes, the method of this invention employs a gentle shearing process with low shearing force and small impact force during dispersion. This avoids damaging the structure and surface morphology of each component in the slurry (a blend of carbon-coated silicon-based material, ion transport medium precursor, dispersant, and solvent), thus preventing irreversible damage to the material and enabling high-speed dispersion without destroying the structure.
[0052] The characteristic of this process is that the slurry (blended material) flows at high speed under external force, generating pressure; the pressure drives the fluid to quickly pass through the narrow slit, and all substances in the slurry are uniformly dispersed under the action of pressure and the narrow slit. This method has high dispersion efficiency and good effect.
[0053] Preferably, the dispersion time in step (2) is 0.1-5h, for example, it can be 0.2h, 0.5h, 0.8h, 1h, 1.2h, 1.5h, 1.8h, 2h, 2.5h, 3h, 3.5h, 4h or 4.5h, as well as specific point values between the above point values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific point values included in the range.
[0054] As a preferred technical solution of the present invention, when dispersion is carried out in the first shearing dispersion device, the slurry formed by carbon-coated silicon-based material, ion transport medium precursor, dispersant and solvent is driven by external force to form high-speed flow, the fluid passes through the slit, and all substances in the slurry are dispersed evenly.
[0055] Preferably, the method for forming microdroplets and drying the dispersion in a second shear dispersion drying apparatus under heat flow conditions to obtain powder includes any one or a combination of at least two of the following A1)-A3):
[0056] A1) Dry gas with a certain temperature passes through the dispersion liquid material layer at a controlled speed. With the assistance of vibration, the material is impacted by the hot gas. The impact shear force causes the material to form micro-droplets and reach a fluidized state. The micro-droplets are dried instantly to obtain powder.
[0057] A2) The dispersion is atomized into small droplets by a high-speed centrifugal disc, or atomized into small droplets under the drive of compressed gas. The small droplets then come into contact with hot air in the drying chamber, evaporate the solvent and form powder. The powder particles are carried away from the drying chamber with the hot air.
[0058] A3) The dispersion is fed into a compact drying chamber, where it comes into contact with hot air and a rotating impeller. The shear force caused by the rotation drive and thermal shock decomposes the dispersion into microdroplets. The microdroplets are dried instantaneously to form powder. The powder product is carried out of the drying chamber along with the hot air.
[0059] Preferably, the second shear dispersion drying device includes any one or a combination of at least two of the following: fluidized bed, airflow flash dryer, two-fluid spray dryer, and centrifugal spray dryer.
[0060] Preferably, the drying temperature is 50-300℃, for example, it can be 60℃, 80℃, 100℃, 120℃, 150℃, 180℃, 200℃, 220℃, 250℃ or 280℃, as well as specific values between the above points. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values included in the range.
[0061] In this invention, the dynamic heat treatment involves subjecting the dried powder to high-temperature heat treatment under dynamic conditions, such as by means of vibration, stirring, or rotation, so that the material particles rub against each other during the heat treatment process to form a complete and uniformly coated ion-transporting artificial SEI film.
[0062] Preferably, the dynamic heat treatment device includes any one or a combination of at least two of the following: rotary kiln, blast drying box, tube furnace, and roller kiln.
[0063] Preferably, the dynamic heat treatment is carried out in an inert atmosphere.
[0064] Preferably, the inert atmosphere includes nitrogen and / or argon.
[0065] Preferably, the rotational speed of the dynamic heat treatment is 1-20 r / min, for example, it can be 2 r / min, 4 r / min, 5 r / min, 6 r / min, 8 r / min, 10 r / min, 12 r / min, 15 r / min or 18 r / min, as well as specific values between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values included in the range.
[0066] Preferably, the temperature of the dynamic heat treatment is 100-1000℃, for example, it can be 200℃, 300℃, 400℃, 500℃, 600℃, 700℃, 800℃ or 900℃, as well as specific values between the above points. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values included in the range.
[0067] Preferably, the dynamic heat treatment time is 0.5-10h, for example, it can be 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h or 9h, as well as specific point values between the above points. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific point values included in the range.
[0068] As a preferred embodiment of the present invention, the preparation method includes the following steps:
[0069] (1) A carbon layer is deposited on a silicon-based core by chemical vapor deposition, wherein the carbon source used in the chemical vapor deposition includes any one or a combination of at least two of acetylene, ethylene, methane, and ethane, the temperature is 400-1000℃, the pressure is 1-10MPa, and the time is 0.5-8h, to obtain a carbon-coated silicon-based material.
[0070] (2) The carbon-coated silicon-based material, ion transport medium precursor, dispersant and solvent are mixed and dispersed in a first shear dispersion device to obtain a dispersion;
[0071] Based on the mass of the carbon-coated silicon-based material being 100%, the mass of the ion transport medium precursor is 0.01%-10%, and the mass of the dispersant is 0.01%-5%.
[0072] (3) The dispersion is dried in a second shear dispersion drying device under heat flow conditions to form microdroplets and obtain powder;
[0073] (4) The powder is subjected to dynamic heat treatment in a dynamic heat treatment device. The rotation speed of the dynamic heat treatment is 1-20 r / min, the temperature is 100-1000℃, and the time is 0.5-10h to obtain the silicon-containing anode material.
[0074] Thirdly, the present invention provides an apparatus for preparing silicon-containing anode materials, the apparatus comprising a reaction device, a first shear dispersion device, a second shear dispersion drying device, and a dynamic heat treatment device connected in sequence.
[0075] Preferably, the silicon-containing anode material as described in the first aspect is prepared by the preparation apparatus.
[0076] Preferably, the reaction apparatus includes a physical vapor deposition apparatus and / or a chemical vapor deposition apparatus, and more preferably a chemical vapor deposition apparatus.
[0077] Preferably, the first shearing and dispersing device includes any one or a combination of at least two of a disperser, a mixer, a homogenizer, and a rotor homogenizing circulation pump, and more preferably a combination of a disperser and a rotor homogenizing circulation pump.
[0078] Preferably, the second shear dispersion drying device includes any one or a combination of at least two of the following: fluidized bed, airflow flash dryer, two-fluid spray dryer, and centrifugal spray dryer.
[0079] Preferably, the dynamic heat treatment device includes any one or a combination of at least two of the following: rotary kiln, blast drying box, tube furnace, and roller kiln.
[0080] Fourthly, the present invention provides a negative electrode material composition comprising a combination of an active material, a binder, and a conductive material, wherein the active material comprises a silicon-containing negative electrode material as described in the first aspect.
[0081] Preferably, the active material includes the silicon-containing anode material and optionally a carbon material, and more preferably a combination of silicon-containing anode material and carbon material.
[0082] Preferably, the carbon material includes any one or a combination of at least two of graphite, carbon black, carbon fiber, mesophase carbon microspheres, and petroleum coke, with graphite being more preferred.
[0083] Preferably, the graphite is natural graphite and / or artificial graphite.
[0084] Preferably, the mass percentage of silicon-containing anode material in the active material is 1-80%, for example, it can be 5%, 10%, 20%, 30%, 40%, 50%, 60% or 70%, and specific values between the above points. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values included in the range, and 20-70% is further preferred.
[0085] Preferably, the mass percentage of active material in the negative electrode material composition is 80-98%, for example, it can be 82%, 85%, 88%, 90%, 92%, 95% or 97%, and specific values between the above points. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values included in the range.
[0086] Preferably, the adhesive comprises any one or a combination of at least two of acrylic polymers, polyacrylonitrile, styrene-based copolymers, and sodium carboxymethyl cellulose (CMC).
[0087] Preferably, the styrene-based copolymer includes styrene-butadiene rubber (SBR).
[0088] Preferably, the mass percentage of the binder in the negative electrode material composition is 0.1-12%, for example, it can be 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or 11%, and specific values between the above points. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values included in the range.
[0089] Preferably, the conductive material includes any one or a combination of at least two of conductive carbon black, graphite, carbon fiber, carbon nanotubes, Ketjen black, and acetylene black.
[0090] Preferably, the mass percentage of conductive material in the negative electrode material composition is 0.1-10%, for example, it can be 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8% or 9%, and specific values between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values included in the range.
[0091] Fifthly, the present invention provides a negative electrode sheet, the negative electrode sheet comprising a current collector and a coating disposed on the current collector, the material of the coating comprising the negative electrode material composition as described in the fourth aspect.
[0092] Preferably, the method for preparing the negative electrode sheet includes: mixing the negative electrode material composition with a solvent to obtain a negative electrode slurry; coating the negative electrode slurry onto a current collector and drying it to obtain the negative electrode sheet.
[0093] Preferably, the drying process further includes a rolling step.
[0094] In a sixth aspect, the present invention provides an electrochemical energy storage device, the electrochemical energy storage device comprising at least one of the silicon-containing negative electrode material as described in the first aspect, the negative electrode material composition as described in the fourth aspect, and the negative electrode sheet as described in the fifth aspect.
[0095] Preferably, the electrochemical energy storage device includes any one of lithium-ion batteries, sodium-ion batteries, supercapacitors, and solid-state batteries, with lithium-ion batteries being more preferred.
[0096] Compared with the prior art, the present invention has the following beneficial effects:
[0097] (1) In the silicon-containing anode material provided by the present invention, the desolvation effect of the electrolyte on the surface of the silicon anode is reduced by the design and mutual compounding of the silicon-based core and the carbon layer and the ion transport type artificial SEI film. The barrier of lithium ion transport at the interface is significantly reduced, so that the silicon-containing anode material has excellent dynamic performance, effectively improves the first-cycle delithiation capacity and cycle performance at different rates of the lithium-ion battery containing it, and makes the battery have lower impedance, higher first-cycle efficiency and faster charging rate, especially in terms of fast charging performance.
[0098] (2) In the preparation method of the silicon-containing anode material provided by the present invention, an atomic layer deposition (ALD)-based surface modification technology is used to uniformly coat the ion transport medium precursor onto the surface of the carbon-coated silicon-based material, forming a thin and complete tightly coated ion transport-type artificial SEI film, which gives the silicon-containing anode material better kinetic performance and excellent cycle performance. The preparation method is simple to operate, low in cost, easy to scale up, and has a very broad application prospect. Detailed Implementation
[0099] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.
[0100] The terms “comprising,” “including,” “having,” “containing,” or any other variations thereof, as used herein, are intended to cover non-exclusive inclusion. For example, a composition, step, method, article, or apparatus that includes the listed elements is not limited to those elements and may also include other elements not expressly listed or elements inherent to such composition, step, method, article, or apparatus.
[0101] "Optionally", "maybe", "any one" means that the matter or event described thereafter may or may not occur, and the description includes both the possibility that the event may occur and the possibility that the event may not occur.
[0102] The indefinite articles “a” and “an” preceding an element or component of this invention do not impose any limitation on the quantity (i.e., number of times) of the element or component. Therefore, “an” or “a” should be interpreted as including one or at least one, and the singular form of an element or component also includes the plural form, unless the quantity clearly refers only to the singular form.
[0103] The terms "one embodiment," "some embodiments," "exemplary," "specific example," or "some examples," etc., used in this invention refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of the invention. In this document, the illustrative expressions of the above terms are not necessarily directed at the same embodiment or example.
[0104] Furthermore, the technical features involved in the various embodiments of the present invention can be combined with each other as long as they do not conflict with each other.
[0105] The following will use several embodiments as examples to describe in detail the specific components and preparation methods of the silicon-containing anode material, its preparation method, the anode sheet, and the lithium-ion battery containing it according to the present invention. However, the silicon-containing anode material, its preparation method, the anode sheet, and the lithium-ion battery containing it according to the present invention are not limited to these embodiments.
[0106] In the following specific embodiments, the silicon-based core, ion transport material, conductive material, and dispersant used are all commercially available chemicals. Specifically, the silicon-based core uses C-1 SC-1800 silicon-carbon composite; sodium alginate uses Maclean S817374; sodium carboxymethyl cellulose uses Maclean C6332; polyacrylic acid uses Maclean P823077, and the corresponding lithium and sodium salts are prepared by neutralizing polyacrylic acid with lithium hydroxide / sodium hydroxide to pH=7-8. The materials used to prepare the negative electrode, positive electrode, and electrolyte are all commercially available chemicals.
[0107] Example 1
[0108] Silicon-containing anode materials and their preparation:
[0109] A silicon-containing anode material includes a silicon-carbon composite, a carbon layer disposed thereon, and an ion-transporting artificial SEI film. The carbon layer is located between the silicon-carbon composite and the ion-transporting artificial SEI film, and the ion-transporting artificial SEI film comprises titanium dioxide. The preparation method of the silicon-containing anode material is as follows:
[0110] (1) CVD method for setting carbon layer: 200g of silicon-carbon composite SC-1800 was placed in a deposition furnace at 500℃, protected by argon gas, and acetylene gas was introduced at 500℃ with a flow rate of 10L / min and a furnace pressure of 6MPa. After continuous gas introduction for 4h, the mixture was cooled to room temperature, thereby coating a carbon layer on the silicon-carbon composite with a carbon layer thickness of 3-30nm, and obtaining carbon-coated silicon-based material;
[0111] (2) Forming an ion-transporting artificial SEI membrane by ALD-like method: Take 100g of carbon-coated silicon-based material obtained in step (1), 0.8g of sodium alginate, and 1g of titanium dioxide nanoparticles (particle size 3-5nm) and add them to a 500mL dispersion tank. 200g of deionized water was added to a dispersion tank and dispersed at a high speed of 1000r / min for 0.5h under the drive of a high-speed disperser. Simultaneously, a rotor homogenizing pump was used to drive the slurry circulation at a rotor speed of 2000r / min and a linear velocity of 14m / s. After dispersion, the slurry was filtered through a 100-mesh sieve, and the filtrate was collected to obtain a dispersion. The dispersion was then passed through a centrifugal spray dryer to obtain microdroplets, which were dried under a heat flow condition at 200℃, and the powder was collected. The powder was placed in a rotary kiln and heated to 500℃ at a rate of 2℃ / min under nitrogen purging, and held at this temperature for 2h at a rotary kiln speed of 5r / min. After the holding period, the powder was cooled to room temperature and collected to obtain the silicon-containing anode material.
[0112] Negative electrode sheet and its preparation:
[0113] The silicon-containing anode material provided in this embodiment is mixed with artificial graphite at a mass ratio of 1:1 to obtain the active material. The active material, single-walled carbon nanotubes, sodium carboxymethyl cellulose (CMC), conductive carbon black Super P, and styrene-butadiene rubber (SBR) are mixed at a mass ratio of 87:1:2:3:7. Deionized water is added as a solvent, and the mixture is stirred under vacuum until the system is homogeneous to obtain an anode slurry with a solid content of 52%. The anode slurry is uniformly coated on the copper foil of the anode current collector, transferred to a vacuum drying oven for drying, and then rolled and punched to obtain small discs, which are the anode sheets.
[0114] Battery manufacturing:
[0115] A coin cell battery was assembled using a lithium metal sheet as the counter electrode, a Celgard 2400 separator, and an electrolyte solution of 1.1M LiPF6. The electrolyte solution included ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC), as well as additives ethylene carbonate (VC), ethylene sulfate (DTD), and 1,3-propanesulfonate lactone (PS). The ratio of EC:EMC:DEC:VC:DTD:PS was 30:50:20:1:1:1 (mass ratio).
[0116] Example 2
[0117] A silicon-containing anode material includes a silicon-carbon composite and a carbon layer and an ion-transporting artificial SEI film disposed thereon. The carbon layer is located between the silicon-carbon composite and the ion-transporting artificial SEI film, and the ion-transporting artificial SEI film includes titanium dioxide. The preparation method of the silicon-containing anode material differs from that of Example 1 only in that the mass of titanium dioxide nanopowder in step (2) is 2g. The types, amounts, preparation steps and process parameters of other materials are the same as those in Example 1, and the silicon-containing anode material is obtained.
[0118] The silicon-containing anode material provided in this embodiment is mixed with artificial graphite at a mass ratio of 1:1 to obtain an active material. The anode sheet is then prepared and a coin cell is assembled using the same method as in Example 1.
[0119] Example 3
[0120] A silicon-containing anode material includes a silicon-carbon composite and a carbon layer and an ion-transporting artificial SEI film disposed thereon. The carbon layer is located between the silicon-carbon composite and the ion-transporting artificial SEI film, and the ion-transporting artificial SEI film includes titanium dioxide. The preparation method of the silicon-containing anode material differs from that of Example 1 only in that the mass of titanium dioxide nanopowder in step (2) is 0.5g. The types, amounts, preparation steps and process parameters of other materials are the same as those in Example 1, and the silicon-containing anode material is obtained.
[0121] The silicon-containing anode material provided in this embodiment is mixed with artificial graphite at a mass ratio of 1:1 to obtain an active material. The anode sheet is then prepared and a coin cell is assembled using the same method as in Example 1.
[0122] Example 4
[0123] A silicon-containing anode material includes a silicon-carbon composite and a carbon layer and an ion-transporting artificial SEI film disposed thereon. The carbon layer is located between the silicon-carbon composite and the ion-transporting artificial SEI film, and the ion-transporting artificial SEI film includes titanium dioxide. The preparation method of the silicon-containing anode material differs from that of Example 1 only in that the particle size of the titanium dioxide nanoparticles in step (2) is 100 nm. The types, amounts, preparation steps and process parameters of other materials are the same as those in Example 1, and the silicon-containing anode material is obtained.
[0124] The silicon-containing anode material provided in this embodiment is mixed with artificial graphite at a mass ratio of 1:1 to obtain an active material. The anode sheet is then prepared and a coin cell is assembled using the same method as in Example 1.
[0125] Example 5
[0126] A silicon-containing anode material includes a silicon-carbon composite and a carbon layer and an ion-transporting artificial SEI film disposed thereon. The carbon layer is located between the silicon-carbon composite and the ion-transporting artificial SEI film, and the ion-transporting artificial SEI film includes aluminum oxide. The preparation method of the silicon-containing anode material differs from that of Example 1 only in that the titanium dioxide nanoparticles in step (2) are replaced with an equal mass of aluminum oxide (particle size 10 nm). The types, amounts, preparation steps and process parameters of other materials are the same as those in Example 1, and the silicon-containing anode material is obtained.
[0127] The silicon-containing anode material provided in this embodiment is mixed with artificial graphite at a mass ratio of 1:1 to obtain an active material. The anode sheet is then prepared and a coin cell is assembled using the same method as in Example 1.
[0128] Example 6
[0129] A silicon-containing anode material includes a silicon-carbon composite and a carbon layer and an ion-transporting artificial SEI film disposed thereon. The carbon layer is located between the silicon-carbon composite and the ion-transporting artificial SEI film, and the ion-transporting artificial SEI film includes lithium silicate. The preparation method of the silicon-containing anode material differs from that of Example 1 only in that the titanium dioxide nanoparticles in step (2) are replaced with an equal mass of lithium silicate (particle size 80 nm). The types, amounts, preparation steps and process parameters of other materials are the same as those in Example 1, and the silicon-containing anode material is obtained.
[0130] The silicon-containing anode material provided in this embodiment is mixed with artificial graphite at a mass ratio of 1:1 to obtain an active material. The anode sheet is then prepared and a coin cell is assembled using the same method as in Example 1.
[0131] Example 7
[0132] A silicon-containing anode material includes a silicon-carbon composite and a carbon layer and an ion-transporting artificial SEI film disposed thereon. The carbon layer is located between the silicon-carbon composite and the ion-transporting artificial SEI film, and the ion-transporting artificial SEI film includes lithium fluoride. The preparation method of the silicon-containing anode material differs from that of Example 1 only in that the titanium dioxide nanoparticles in step (2) are replaced with an equal mass of lithium fluoride (particle size 10 nm). The types, amounts, preparation steps and process parameters of other materials are the same as those in Example 1, and the silicon-containing anode material is obtained.
[0133] The silicon-containing anode material provided in this embodiment is mixed with artificial graphite at a mass ratio of 1:1 to obtain an active material. The anode sheet is then prepared and a coin cell is assembled using the same method as in Example 1.
[0134] Example 8
[0135] A silicon-containing anode material includes a silicon-carbon composite and a carbon layer and an ion-transporting artificial SEI film disposed thereon. The carbon layer is located between the silicon-carbon composite and the ion-transporting artificial SEI film, and the ion-transporting artificial SEI film includes silicon dioxide. The preparation method of the silicon-containing anode material differs from that of Example 1 only in that the titanium dioxide nanoparticles in step (2) are replaced with an equal mass of silicon dioxide (particle size 10 nm). The types, amounts, preparation steps and process parameters of other materials are the same as those in Example 1, and the silicon-containing anode material is obtained.
[0136] The silicon-containing anode material provided in this embodiment is mixed with artificial graphite at a mass ratio of 1:1 to obtain an active material. The anode sheet is then prepared and a coin cell is assembled using the same method as in Example 1.
[0137] Example 9
[0138] A silicon-containing anode material includes a silicon-carbon composite and a carbon layer and an ion-transporting artificial SEI film disposed thereon. The carbon layer is located between the silicon-carbon composite and the ion-transporting artificial SEI film. The ion-transporting artificial SEI film includes titanium dioxide and carbon nanotubes. The preparation method of the silicon-containing anode material differs from that of Example 1 only in that the titanium dioxide nanopowder in step (2) is replaced with 0.8g of titanium dioxide nanopowder and 0.2g of carbon nanotubes (particle size 80nm). The types, amounts, preparation steps and process parameters of other materials are the same as those in Example 1, and the silicon-containing anode material is obtained.
[0139] The silicon-containing anode material provided in this embodiment is mixed with artificial graphite at a mass ratio of 1:1 to obtain an active material. The anode sheet is then prepared and a coin cell is assembled using the same method as in Example 1.
[0140] Example 10
[0141] A silicon-containing anode material includes a silicon-carbon composite and a carbon layer and an ion-transporting artificial SEI film disposed thereon. The carbon layer is located between the silicon-carbon composite and the ion-transporting artificial SEI film. The ion-transporting artificial SEI film includes titanium dioxide and conductive carbon black. The preparation method of the silicon-containing anode material differs from that of Example 1 only in that the titanium dioxide nanopowder in step (2) is replaced with 0.8g of titanium dioxide nanopowder and 0.2g of conductive carbon black (particle size 80nm). The types, amounts, preparation steps and process parameters of other materials are the same as those in Example 1, and the silicon-containing anode material is obtained.
[0142] The silicon-containing anode material provided in this embodiment is mixed with artificial graphite at a mass ratio of 1:1 to obtain an active material. The anode sheet is then prepared and a coin cell is assembled using the same method as in Example 1.
[0143] Example 11
[0144] A silicon-containing anode material includes a silicon-carbon composite and a carbon layer and an ion-transporting artificial SEI film disposed thereon. The carbon layer is located between the silicon-carbon composite and the ion-transporting artificial SEI film, and the ion-transporting artificial SEI film includes titanium dioxide. The preparation method of the silicon-containing anode material differs from that of Example 1 only in that 0.8g of sodium alginate in step (2) is replaced with 5g of acrylate homopolymer lithium salt. The types, amounts, preparation steps and process parameters of other materials are the same as those in Example 1, and the silicon-containing anode material is obtained.
[0145] The silicon-containing anode material provided in this embodiment is mixed with artificial graphite at a mass ratio of 1:1 to obtain an active material. The anode sheet is then prepared and a coin cell is assembled using the same method as in Example 1.
[0146] Example 12
[0147] A silicon-containing anode material includes a silicon-carbon composite and a carbon layer and an ion-transporting artificial SEI film disposed thereon, wherein the carbon layer is located between the silicon-carbon composite and the ion-transporting artificial SEI film, and the ion-transporting artificial SEI film includes titanium dioxide; the preparation method of the silicon-containing anode material differs from that of Example 1 only in that the drying temperature under heat flow conditions in step (2) is 500°C; the type, amount, preparation steps and other process parameters of the materials are the same as those of Example 1, and the silicon-containing anode material is obtained.
[0148] The silicon-containing anode material provided in this embodiment is mixed with artificial graphite at a mass ratio of 1:1 to obtain an active material. The anode sheet is then prepared and a coin cell is assembled using the same method as in Example 1.
[0149] Example 13
[0150] A silicon-containing anode material includes a silicon-carbon composite and a carbon layer and an ion-transporting artificial SEI film disposed thereon, wherein the carbon layer is located between the silicon-carbon composite and the ion-transporting artificial SEI film, and the ion-transporting artificial SEI film includes titanium dioxide; the preparation method of the silicon-containing anode material differs from that of Example 1 only in that the holding temperature (dynamic heat treatment temperature) of the rotary kiln in step (2) is 1000℃; the type, amount, preparation steps and other process parameters of the materials are the same as those of Example 1, and the silicon-containing anode material is obtained.
[0151] The silicon-containing anode material provided in this embodiment is mixed with artificial graphite at a mass ratio of 1:1 to obtain an active material. The anode sheet is then prepared and a coin cell is assembled using the same method as in Example 1.
[0152] Example 14
[0153] A silicon-containing anode material includes a silicon-carbon composite and a carbon layer and an ion-transporting artificial SEI film disposed thereon. The carbon layer is located between the silicon-carbon composite and the ion-transporting artificial SEI film, and the ion-transporting artificial SEI film includes titanium dioxide. The preparation method of the silicon-containing anode material differs from that of Example 1 only in that the holding temperature (dynamic heat treatment temperature) of the rotary kiln in step (2) is 800°C. The types, amounts, preparation steps and process parameters of other materials are the same as those in Example 1, and the silicon-containing anode material is obtained.
[0154] The silicon-containing anode material provided in this embodiment is mixed with artificial graphite at a mass ratio of 1:1 to obtain an active material. The anode sheet is then prepared and a coin cell is assembled using the same method as in Example 1.
[0155] Comparative Example 1
[0156] A silicon-containing anode material, namely the silicon-carbon composite SC-1800 in Example 1, was used without any surface treatment.
[0157] The silicon-containing anode material in this comparative example was mixed with artificial graphite at a mass ratio of 1:1 to obtain the active material. The anode sheet was prepared and a coin cell was assembled using the same method as in Example 1.
[0158] Comparative Example 2
[0159] A silicon-containing anode material includes a silicon-carbon composite and a carbon layer disposed thereon; the difference between the preparation method of the silicon-containing anode material and Example 1 is that step (2) is not performed, that is, the carbon layer is disposed by CVD method in step (1) to obtain the silicon-containing anode material.
[0160] The silicon-containing anode material provided in this comparative example was mixed with artificial graphite at a mass ratio of 1:1 to obtain an active material. The anode sheet was prepared and a coin cell was assembled using the same method as in Example 1.
[0161] Comparative Example 3
[0162] A silicon-containing anode material includes a silicon-carbon composite and an ion-transporting artificial SEI film disposed thereon; the preparation method of the silicon-containing anode material differs from that of Example 1 only in that step (1) is omitted, that is, the carbon-coated silicon-based material in step (2) of Example 1 is replaced with an equal mass of silicon-carbon composite SC-1800, and the types, amounts, preparation steps and process parameters of other materials are the same as those in Example 1, so as to obtain the silicon-containing anode material.
[0163] The silicon-containing anode material provided in this comparative example was mixed with artificial graphite at a mass ratio of 1:1 to obtain an active material. The anode sheet was prepared and a coin cell was assembled using the same method as in Example 1.
[0164] Comparative Example 4
[0165] A silicon-containing anode material includes a silicon-carbon composite and a carbon layer and an ion-transporting artificial SEI film disposed thereon. The carbon layer is located between the silicon-carbon composite and the ion-transporting artificial SEI film, and the ion-transporting artificial SEI film includes titanium dioxide. The preparation method of the silicon-containing anode material differs from that of Example 1 only in that sodium alginate is not added in step (2). The types, amounts, preparation steps and process parameters of other materials are the same as those in Example 1, and the silicon-containing anode material is obtained.
[0166] The silicon-containing anode material provided in this comparative example was mixed with artificial graphite at a mass ratio of 1:1 to obtain an active material. The anode sheet was prepared and a coin cell was assembled using the same method as in Example 1.
[0167] Comparative Example 5
[0168] A silicon-containing anode material includes a silicon-carbon composite, a carbon layer disposed thereon, and an ion-transporting artificial SEI film. The carbon layer is located between the silicon-carbon composite and the ion-transporting artificial SEI film, and the ion-transporting artificial SEI film comprises titanium dioxide. The preparation method of the silicon-containing anode material is as follows:
[0169] (1) Carbon layer formation by CVD method: Same as in Example 1, carbon-coated silicon-based material is obtained;
[0170] (2) Formation of an ion-transporting artificial SEI membrane: Take 100g of carbon-coated silicon-based material obtained in step (1), 0.8g of sodium alginate, and 1g of titanium dioxide nanoparticles (particle size 3-5nm) and add them to a 500mL dispersion tank. Add 200g of deionized water to the dispersion tank and disperse at a high speed of 1000r / min for 0.5h under the drive of a high-speed disperser. After dispersion, filter through a 100-mesh sieve and collect the filtrate to obtain a dispersion. Disperse the dispersion into microdroplets through a centrifugal spray dryer and dry it under a heat flow condition of 200℃ to collect the powder. Place the powder in a rotary kiln and heat it to 500℃ at a rate of 2℃ / min under nitrogen purging. Hold it at this temperature for 2h, and the rotary kiln speed is 5r / min. After holding at this temperature, cool it to room temperature and collect the powder to obtain the silicon-containing anode material.
[0171] The silicon-containing anode material provided in this comparative example was mixed with artificial graphite at a mass ratio of 1:1 to obtain an active material. The anode sheet was prepared and a coin cell was assembled using the same method as in Example 1.
[0172] Comparative Example 6
[0173] A silicon-containing anode material includes a silicon-carbon composite, a carbon layer disposed thereon, and an ion-transporting artificial SEI film. The carbon layer is located between the silicon-carbon composite and the ion-transporting artificial SEI film, and the ion-transporting artificial SEI film comprises titanium dioxide. The preparation method of the silicon-containing anode material is as follows:
[0174] (1) Carbon layer formation by CVD method: Same as in Example 1, carbon-coated silicon-based material is obtained;
[0175] (2) Formation of ion-transporting artificial SEI membrane: Take 100g of carbon-coated silicon-based material obtained in step (1), 0.8g of sodium alginate, and 1g of titanium dioxide nanoparticles (particle size 3-5nm) and add them to a 500mL dispersion tank. Add 200g of deionized water to the dispersion tank and disperse at a high speed of 1000r / min for 0.5h under the drive of a high-speed disperser; at the same time, drive the slurry circulation with a rotor homogenizing pump, the rotor speed is 2000r / min, and the linear velocity is 14m / s; after dispersion, filter with a 100-mesh sieve, collect the filtrate, and obtain the dispersion; dry the dispersion directly through a forced-air drying oven at a temperature of 200℃, and deagglomerate after drying to obtain powder; place the powder in a rotary kiln, heat it to 500℃ at a rate of 2℃ / min under nitrogen conditions, keep it at the temperature for 2h, and the rotary kiln speed is 5r / min; after the heat preservation is completed, cool it to room temperature, collect the powder, and obtain the silicon-containing anode material.
[0176] The silicon-containing anode material provided in this comparative example was mixed with artificial graphite at a mass ratio of 1:1 to obtain an active material. The anode sheet was prepared and a coin cell was assembled using the same method as in Example 1.
[0177] Comparative Example 7
[0178] A silicon-containing anode material includes a silicon-carbon composite and a carbon layer and an ion-transporting artificial SEI film disposed thereon, wherein the carbon layer is located between the silicon-carbon composite and the ion-transporting artificial SEI film, and the ion-transporting artificial SEI film includes titanium dioxide; the preparation method of the silicon-containing anode material differs from that of Example 1 only in that the rotation speed of the rotary kiln in step (2) is 0 (i.e., static heat treatment at 500°C for 2 hours); the type, amount, preparation steps and other process parameters of the materials are the same as those of Example 1, and the silicon-containing anode material is obtained.
[0179] The silicon-containing anode material provided in this embodiment is mixed with artificial graphite at a mass ratio of 1:1 to obtain an active material. The anode sheet is then prepared and a coin cell is assembled using the same method as in Example 1.
[0180] The following performance tests were conducted on the silicon-containing anode material and battery provided above:
[0181] (1) Median particle size of silicon-containing anode materials: The median particle size (D) of silicon-containing anode materials was measured using a Malvern laser particle size analyzer. 50 Particle size);
[0182] (2) Specific surface area of silicon-containing anode materials: The specific surface area of the samples was tested using a Microt TriStar 3000 specific surface analyzer.
[0183] (3) Initial charge / discharge mode: 0.1C-0.02C / 0.1C, voltage range 0.005-1.5V, to obtain the first week lithium removal capacity of the battery;
[0184] (4) Low-rate charge-discharge test: 0.2C rate charging, 0.2C rate discharging, voltage range 0.005-1.5V, the battery is cycled for 30 cycles; the capacity retention rate is calculated after the cycle test;
[0185] (5) High-rate charge-discharge test: 1.5C rate charging, 0.2C rate discharging, voltage range 0.005-1.5V, the battery is cycled for 30 cycles; the capacity retention rate is calculated after the cycle test;
[0186] 30-week cycle capacity retention = 100% × delithiation capacity in week 30 / delithiation capacity in week 1;
[0187] (6) First-time efficiency test: The batteries prepared above were formed and capacity tested using a battery test cabinet. The formation process was to charge at a constant current of 0.05C for 2 hours, and then charge at a constant current of 0.15C for 2.5 hours; the capacity testing process was to charge at a constant current of 0.33C to 4.2V, and then charge at a constant voltage of 4.2V to the cutoff current of 0.02C, and then discharge at 0.33C to 2.5V; the sum of the above charging capacity and the discharge capacity were recorded as the first charging capacity and the first discharging capacity, and the first coulombic efficiency was calculated.
[0188] (7) Impedance test: Under the condition of 25℃ and 50% SOC, the internal resistance DCR is tested by an internal resistance meter (model AinuoANBTS7501H).
[0189] The test results are shown in Table 1:
[0190] Table 1
[0191]
[0192]
[0193] According to the test results in Table 1, the silicon-containing anode material provided by this invention comprises a three-layer structure consisting of a silicon-based core, a carbon layer, and an ion-transporting artificial SEI film. The ion-transporting artificial SEI film is prepared using an ALD-like technology, uniformly and tightly wrapping the ion-transporting medium on the material surface. Through the design and mutual compounding of the multi-layer structure, the lithium-ion desolvation energy barrier is reduced, enhancing the ion-conducting capability of the silicon-containing anode material surface. This results in significantly improved kinetic performance of the silicon-containing anode material, leading to high first-cycle lithium stripping capacity in batteries containing it, significantly improved cycle performance at different rates, and effective improvement in fast-charging performance. This technology helps silicon-containing anode materials to be better applied in fast-charging batteries.
[0194] Furthermore, a comparison of Examples 1-3 shows that nano-titanium dioxide, as an ion transport medium, forms an ion-transporting artificial SEI film that can improve the cycling performance of silicon-containing anode materials at high rates. With increasing amounts of nano-titanium dioxide, the kinetic performance of the silicon-containing anode material increases, but remains essentially unchanged after reaching a threshold. A comparison of Examples 1, 4, and 5 shows that small-particle-size ion transport media have a beneficial effect on kinetic improvement, and nanoparticles such as alumina can achieve similar technical effects. A comparison of Examples 1 and Examples 6-10 shows that different types of ion transport materials (fast ion conductors) can improve the fast-charging performance of silicon anode materials, with the improvement effect influenced by the type of fast ion conductor. Simultaneously, an ion-transporting artificial SEI film formed by combining fast ion conductors and conductive materials can achieve kinetic improvement. Examples 11-14 demonstrate that the performance of silicon-containing anode materials can be controlled and optimized by setting process parameters such as the type of dispersant and temperature.
[0195] As can be seen from the comparison of Example 1 and Comparative Examples 1-3, the carbon layer and ion-transporting artificial SEI film introduced on the surface of the silicon-based core in this invention are crucial for improving the kinetic performance and high-rate cycling performance of silicon-containing anode materials. Both are indispensable, and the absence of either one will lead to a significant reduction in the performance of silicon-containing anode materials and batteries.
[0196] As can be seen from the comparison of Example 1 and Comparative Examples 4-7, the ALD-like coating technology proposed in this invention is crucial for the formation and coating of ion-transporting artificial SEI films. This technology can make the ion transport medium uniformly distributed and tightly coated on the surface of the silicon-containing anode material. If a dispersant is not introduced, or if low-shear dispersion is not carried out in the first shear dispersion device, or if drying is not carried out in the second shear dispersion drying device and under heat flow conditions, or if dynamic heat treatment is not carried out, the ion transport medium will be unevenly distributed on the surface of the silicon-containing anode material, and the resulting product cannot achieve improved kinetic performance and high-rate cycling performance.
[0197] The applicant declares that this invention illustrates the silicon-containing anode material, its preparation method, and its application through the above embodiments. However, this invention is not limited to the above embodiments, meaning that this invention does not necessarily rely on the above embodiments for implementation. Those skilled in the art should understand that any improvements to this invention, equivalent substitutions of raw materials, additions of auxiliary components, and selection of specific methods, etc., all fall within the protection and disclosure scope of this invention.
Claims
1. A silicon-containing anode material, characterized in that, The silicon-containing anode material includes a silicon-based core and a carbon layer and an ion-transporting artificial SEI film disposed on the silicon-based core, wherein the carbon layer is located between the silicon-based core and the ion-transporting artificial SEI film.
2. The silicon-containing anode material according to claim 1, characterized in that, The ion-transporting artificial SEI membrane includes ion-transporting materials and / or conductive materials; Preferably, the ion transport material comprises any one or a combination of at least two of the following: lithium salt, lithium oxide, transition metal oxide, transition metal phosphide, transition metal sulfide, half-metal oxide, elemental phosphorus, elemental sulfur, and other solid electrolytes. Preferably, the ion transport material comprises any one or a combination of at least two of the following: lithium carbonate, lithium silicate, lithium metasilicate, lithium phosphate, lithium metaphosphate, lithium hypophosphite, lithium borate, lithium titanate, lithium oxide, lithium fluoride, lithium aluminate, lithium phosphide, lithium sulfide, lithium nickelate, calcium oxide, zinc oxide, aluminum oxide, zirconium oxide, zirconium nitride, zirconium phosphide, molybdenum oxide, molybdenum nitride, molybdenum phosphide, molybdenum sulfide, molybdenum borate, silicon suboxide, silicon dioxide, titanium dioxide, elemental phosphorus, elemental sulfur, other oxide solid electrolytes, and other sulfide solid electrolytes. Preferably, the average particle size of the ion transport material is 1-1000 nm; Preferably, the conductive material includes any one or a combination of at least two of graphene, carbon nanotubes, conductive carbon black, amorphous carbon, soft carbon, and hard carbon. Preferably, the ion-transporting artificial SEI membrane comprises an ion-transporting material and / or a conductive material, and the ion-transporting artificial SEI membrane has at least one of the following structures: A-D. Structure A: Composed of ion transport materials; Structure B: Composed of conductive materials; Structure C: The conductive material is distributed within the ion transport material; Structure D: The ion transport material is distributed within the conductive material; Preferably, the mass of the ion-transporting artificial SEI film is 0.01%-15% based on the total mass of the silicon-based core and carbon layer as 100%.
3. The silicon-containing anode material according to claim 1 or 2, characterized in that, The thickness of the carbon layer is 1-30 nm; Preferably, the carbon layer comprises 0.01%-10% of the silicon-based core by mass, which is 100% of the total mass.
4. The silicon-containing anode material according to claim 1 or 2, characterized in that, The silicon-based core includes any one or a combination of at least two of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite, and silicon alloy; Preferably, the median particle size of the silicon-containing anode material is 1-30 μm, and more preferably 2-20 μm; Preferably, the specific surface area of the silicon-containing anode material is 0.1-20 m². 2 / g, further optimized to 1-10m 2 / g.
5. A method for preparing a silicon-containing anode material as described in any one of claims 1-4, characterized in that, The preparation method employs an atomic layer deposition-like method, including the following steps: (1) A carbon layer is set on a silicon-based core to obtain a carbon-coated silicon-based material; (2) The carbon-coated silicon-based material, ion transport medium precursor, dispersant and solvent are mixed and dispersed in a first shear dispersion device to obtain a dispersion. (3) The dispersion is dried in a second shear dispersion drying device under heat flow conditions to form microdroplets and obtain powder; (4) The powder is subjected to dynamic heat treatment in a dynamic heat treatment device to obtain the silicon-containing anode material.
6. The preparation method according to claim 5, characterized in that, The dispersant comprises any one or a combination of at least two of the following: carboxymethyl cellulose salt, alginate, homopolymer salt of (meth)acrylic acid, and copolymer salt of (meth)acrylic acid. Preferably, the mass of the dispersant is 0.01%-5% based on 100% of the mass of the carbon-coated silicon-based material; Preferably, the solvent is water; Preferably, the mass of the solvent is 50%-500% based on 100% of the mass of the carbon-coated silicon-based material; Preferably, the first shearing and dispersing device includes any one or a combination of at least two of a disperser, a mixer, a homogenizer, and a rotor homogenizing circulation pump; Preferably, the dispersion time in step (2) is 0.1-5 hours; Preferably, the second shear dispersion drying device includes any one or a combination of at least two of the following: a fluidized bed, an air flash dryer, a two-fluid spray dryer, and a centrifugal spray dryer; Preferably, the drying temperature is 50-300℃; Preferably, the dynamic heat treatment device includes any one or a combination of at least two of the following: rotary kiln, blast drying box, tube furnace, and roller kiln; Preferably, the rotational speed of the dynamic heat treatment is 1-20 r / min; Preferably, the temperature of the dynamic heat treatment is 100-1000℃; Preferably, the dynamic heat treatment time is 0.5-10 hours.
7. An apparatus for preparing silicon-containing anode materials, characterized in that, The preparation apparatus includes a reaction device, a first shear dispersion device, a second shear dispersion drying device, and a dynamic heat treatment device connected in sequence. Preferably, the silicon-containing anode material as described in any one of claims 1-4 is prepared using the aforementioned preparation apparatus; Preferably, the reaction apparatus includes a physical vapor deposition apparatus and / or a chemical vapor deposition apparatus; Preferably, the first shearing and dispersing device includes any one or a combination of at least two of a disperser, a mixer, a homogenizer, and a rotor homogenizing circulation pump; Preferably, the second shear dispersion drying device includes any one or a combination of at least two of the following: a fluidized bed, an air flash dryer, a two-fluid spray dryer, and a centrifugal spray dryer; Preferably, the dynamic heat treatment device includes any one or a combination of at least two of the following: rotary kiln, blast drying box, tube furnace, and roller kiln.
8. A negative electrode material composition, characterized in that, The negative electrode material composition comprises a combination of an active material, a binder, and a conductive material, wherein the active material comprises a silicon-containing negative electrode material as described in any one of claims 1-4.
9. A negative electrode sheet, characterized in that, The negative electrode sheet includes a current collector and a coating disposed on the current collector, wherein the material of the coating includes the negative electrode material composition as described in claim 8.
10. An electrochemical energy storage device, characterized in that, The electrochemical energy storage device includes at least one of the silicon-containing anode material as described in any one of claims 1-4, the anode material composition as described in claim 8, and the anode sheet as described in claim 9; Preferably, the electrochemical energy storage device includes any one of lithium-ion batteries, sodium-ion batteries, supercapacitors, and solid-state batteries.
Citation Information
Patent Citations
Silicon negative electrode material and preparation method thereof, negative electrode plate and electrochemical device
CN117976878A
Silicon-based negative electrode material with composite artificial SEI film and preparation method and application of silicon-based negative electrode material
CN118380575A
Artificial SEI film coated silicon negative electrode active material and preparation method thereof
CN118472205A
